ANALISIS KUALITAS PELAYANAN KA COMMUTER LINE RUTE PARUNGPANJANG-TANAH ABANG - Efendy Tambunan (UKI Press, 2020)
The growth of Jakarta's population and many of them have been moving and settled in the buffer zones of Jakarta. Its impact is on increasing the number of movement of commuters from the buffer zones to Jakarta city. Indonesian Commuter Line (KCI) is the most reliable mass transportation mode as public transportation from the buffer zones of Jakarta such as Bodetabek (Bogor, Depok, Tangerang and Bekasi) to Jakarta. The annual growth in the number of passengers and the limited infrastructure of commuter line can impact on decreasing the quality of operational services, both in terms of the train's punctuality and travel time as the dominant variable in determining the quality operational services. Therefore it’s necessary to evaluate whether the annual growth in the number of passengers can has the impact on decreasing the quality of operational services of commuter line. This research is focused on the Parungpanjang–Tanah Abang route using descriptive and quantitative methods. The result of this research shows that the reliability level of the the quality of the operational services of Commuter Line during peak hours is still below the tolerance limit or relatively good.